Comparison of Color Flow Duplex Study with Digital Subtraction Angiography in the Evaluation of Peripheral Vascular Disease - Dr. Mubbashir Latif; Dr. Sajjad Hussain; Dr. Muhammad Abbas; Dr. Adnan Ahmad; Dr. Aanab Sardar; Dr. Muhammad Salman Naz (Indus Journal of Bioscience Research, 2024)
Background: A common vascular disorder marked by constriction or blockage of peripheral arteries, which lowers blood flow and causes ischemia and raises limb morbidity risk is peripheral arterial disease (PAD). Objectives: To assess in suspected cases the diagnostic agreement between Digital Subtraction Angiography (DSA) and Color Doppler Ultrasound (CDUS) in diagnosis of PAD. Methods: We carried out this cross-sectional study over six months. Using non-probability consecutive sampling, 76 patients total, 40–80 years with Ankle-Brachial Index (ABI) of 0.9 were included. Patients excluded were those with baseline serum creatinine more than 1.1 mg/dL or those undergoing hormonal, radiation, or surgical treatment. Every individual had DSA as well as CDUS. Using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and Kappa statistics, CDUS data were matched to DSA, the reference standard, to assess diagnostic performance. Results: For artery stenosis (≥50%), CDUS demonstrated the sensitivity of 94.0% and specificity of 87.5%. PPV was 95.5%; NPV was 85.7%. Strong agreement between CDUS and DSA was demonstrated by Kappa coefficient (κ = 0.81), p < 0.001. With agreement rates of 85.7, 90.9, 92.3 and 87.5%, CDUS appropriately categorized mild, moderate, severe stenosis and full occlusion, correspondingly. In diabetic, hypertensive, smoking and hyperlipidemic subgroups, stratification by risk variables revealed constant performance. Conclusion: Finally, with great concordance with DSA, CDUS is dependable and non-invasive diagnostic instrument for assessing PAD. Especially in situations when invasive angiography is not practical, it is a good substitute for PAD screening since it correctly detects and diagnoses stenosis degree and occlusion.